Private sector rice stocks in Bangladesh: Estimates from the Bangladesh Millers’ and Traders’ Survey (MATS) 2018 - Dorosh, Paul A.; Minot, Nicholas; Kabir, Razin; Hossain, Shahadat (International Food Policy Research Institute, 2021)
Bangladesh has a complex rice value chain consisting of farmers, upstream paddy wholesalers and intermediaries, millers, and downstream rice traders, wholesalers and retailers. Each of these actors serve distinct functions and have lines of trade that affect their stock turnover in different ways. There is a lack of complete information on the volume of rice traded and stored by the private sec-tor. This leads to difficulties in the timeliness of requisite actions on the part of the govern-ment. When rice prices spike, the typical response has been to lay the blame at the feet of millers and traders. For the government, it is important to have a general picture of the level of private stocks in a given year to ensure appropriate adjustments in procurement, distribution and import de-cisions can be made to meet their food security and price stabilization objectives.